2011
DOI: 10.1371/journal.pbio.1000598
|View full text |Cite
|
Sign up to set email alerts
|

Host Defense against Viral Infection Involves Interferon Mediated Down-Regulation of Sterol Biosynthesis

Abstract: Upon infection, our immune cells produce a small protein called interferon, which in turn signals a protective response through a series of biochemical reactions that involves lowering the cells' ability to make cholesterol by targeting a gene essential for controlling the pathway for cholesterol metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
256
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(275 citation statements)
references
References 69 publications
16
256
2
1
Order By: Relevance
“…In contrast, incubation with LCL exosomes induced antiviral response-related pathways including sterol metabolic and biosynthetic processes in the DCs. Sterol-associated biochemistry was recently implicated in type I IFN-driven antiviral immunity induced by viral infection (26). In fact, type I IFN-stimulated genes (ISGs) were among the most strongly induced genes in DCs exposed to LCL exosomes.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, incubation with LCL exosomes induced antiviral response-related pathways including sterol metabolic and biosynthetic processes in the DCs. Sterol-associated biochemistry was recently implicated in type I IFN-driven antiviral immunity induced by viral infection (26). In fact, type I IFN-stimulated genes (ISGs) were among the most strongly induced genes in DCs exposed to LCL exosomes.…”
Section: Resultsmentioning
confidence: 99%
“…We investigated cholesterol profiles as a potential biomarker for IFN- therapy in MS based on a report that type 1 IFN treatment caused coordinated changes in the expression of genes involved in sterol synthesis (21). We found that each 10 mg/dl of greater baseline LDL cholesterol (LDL-C), total cholesterol (TC), and apoB was associated with a 7.4%, 5.9%, and 16% increase in the number of new T2 lesions over 2 years of IFN- treatment, respectively (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Newer laboratory evidence shows that the interferon response to viral infection of the innate immune immune system is coupled to the mevalonate-isoprenoid arm of the sterol pathway. These findings may explain the observation that the CMV and HCV viruses are sensitive to statin administration and that treatment with interferon decreases plasma cholesterol levels similar to treatment with statins (Blanc M et al, 2011). Several observational studies in patients with severe bacterial infections have reported improved survival in patients treated with statins (Bjoerkheim-Bergman et al, 2010).…”
Section: Statinsmentioning
confidence: 94%